The Guantanamo Lawyers : Inside a Prison Outside the Law. - Denbeaux, Mark P. (NYU Press, 2009)
Read free excerpts from the book at http://www.theguantanamolawyers.com and explore the complete archive of narratives at http://dlib.nyu.edu/guantanamo. Following the terrorist attacks of 9/11, the United States imprisoned more than seven hundred and fifty men at its naval base at Guantánamo Bay, Cuba. These men, ranging from teenage boys to men in their eighties from over forty different countries, were detained for years without charges, trial, and a fair hearing. Without any legal status or protection, they were truly outside the law: imprisoned in secret, denied communication with their f.